Análise comparativa do uso de ferramentas de metal duro sem revestimento e revestidas com diboreto de titânio na usinagem da madeira - Celestino, Valter Roberto de Brito [UNESP] (2015)
The use of machining processes to shape and finish will wood has been greatly expanded in recent years, driven by the need for parts that contain a better surface finish tied will good productivity is achieved by continuous improvement of equipment and tools to process wood. This study used an experimental turning system with a new tool holder head, containing power sensors, vibration and acoustic emission engaged in a lathe EMCO Compact 5, very common for teaching procedures, adapted for the processing of wood pinus spp and eucalyptus spp, to demonstrate the use of the process instrumentation, can positively influence the analysis of some parameters such as the average roughness (Ra), total toughness (Rt), plus the acoustic emission values, cutting performance and vibration. Data collection was efficient and accurate for the main parameters of forward speeds at 40 mm/min, 70 mm/min and 100 mm/min and variations of the cutting depth of 0.5 mm; 1.0 mm; and 1.5 mm; with constant surface speed, and the use of two carbide tools, consisting of a polished carbide and uncoated and coated other tool with titanium diboride. The main results obtained, it is noted that the coating tool did not influence the average roughness, and provided lower total roughness and consumed power, but showed higher values for vibration and acoustic emission captured during the experiments. Regarding the type of wood, obtained data are consistent, except for the consumed power values, which may be linked to characteristics of used pieces of wood